FUNCTIONAL STATE OF LIVER IN PATIENTS WITH PERMANENT ATRIAL FIBRILLATION AND COMORBID CHRONIC DIFFUSE INFLAMMATORY LIVER DISEASES BY CONTINUOUS WARFARIN THERAPY - Драпчак, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
We examined 241 patients with ischemic heart disease (IHD), complicated atrial fibrillation that get continuous antiplatelet and anticoagulant therapy. Patients were divided into two groups: 189 patients with chronic diffuse inflammatory liver diseases and 52 patients with comorbid liver diseases. We examined contents of aminotransferases – ASAT, ALT and γ-glutamyltransferase, cholesterol, HDL cholesterol and triglycerides. It was also evaluated liver structure and size with the help of ultrasound imaging per diffuse inflammatory liver diseases criteria. Performed examinations show that individual continuous warfarin therapy in patients with IHD complicated with atrial fibrillation and comorbid chronic liver diseases causes more frequently a significantly severe hepatic damage in comparison to patients without the comorbidity. This is manifested by foremost more frequent disorders of blood biochemistry in these patients, namely increasing of ASAT, ALT, gamma-GT, total cholesterol and triglycerides that gives a high atherogenic coefficient and thereafter an increased risk of cardiovascular complications. In most cases these patient present also often signs of liver increasing with accumulation of adipose tissue and disorder of its structure according to ultrasound imaging results.